An analysis of the generalization and maintenance of eye contact taught during play. (20th December 2012) - Ninci, Jennifer; Lang, Russell; Davenport, Katy; Lee, Allyson; Garner, Jennifer; Moore, Melissa; Boutot, Amanda; Rispoli, Mandy; Lancioni, Giulio
Abstract : Purpose: Differential reinforcement and most-to-least prompting were implemented within the context of developmentally appropriate play activities in an effort to improve the eye contact between a 4-year-old boy with pervasive developmental disorder-not otherwise specified (PDD-NOS) and his three therapists. Methods: A multiple baseline design across therapists was used to examine the eye contact of a 4-year-old boy with PDD-NOS. Maintenance data were collected at 1, 2 and 3 months post intervention. Results: The intervention was effective and improvements in eye contact were maintained for at least 3 months post intervention. However, eye contact did not readily generalize across communication partners. Conclusions: Results suggest that eye contact may not generalize to communication partners who are not directly involved in intervention. Results are discussed in terms of implications for practitioners and directions for future research.